PENGARUH PERCEIVED VALUE DAN TRUST TERHADAP INTENTION TO RECOMMEND DENGAN SATISFACTION SEBAGAI VARIABEL MEDIASI (STUDI PADA APLIKASI BIBIT) - Fransiska Dianita Viorentina (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to examine perceived value and trust that can influence intention to recommend to users of online mutual fund investment applications, namely Bibit, with satisfaction as the mediating variable. The type of this study is a quantitative approach. The population were individuals who had used the service of Bibit application and the samples were 160 respondents. The data analysis technique used is partial least squares. The results of the study show that trust has a positive effect on satisfaction and intention to recommend, and satisfaction itself has a positive effect on intention to recommend. On the other hand, perceived value does not have a positive effect on satisfaction and intention to recommend. Last, the satisfaction variable has a positive effect in mediating the effect of trust on intention to recommend, but does not have a positive effect in mediating the effect of perceived value on intention to recommend. Keywords: perceived value, trust, satisfaction, intention to recommend, and online investment application.